Disassembly of Simian Virus 40 during Passage through the Endoplasmic Reticulum and in the Cytoplasm - Kuksin, Dmitry (American Society for Microbiology, 2012)
The nonenveloped polyomavirus simian virus 40 (SV40) is taken up into cells by a caveola-mediated endocytic process that delivers the virus to the endoplasmic reticulum (ER). Within the ER lumen, the capsid undergoes partial disassembly, which exposes its internal capsid proteins VP2 and VP3 to immunostaining with antibodies. We demonstrate here that the SV40 genome does not become accessible to detection while the virus is in the ER. Instead, the genome becomes accessible two distinct detection procedures, one using anti-bromodeoxyuridine antibodies and the other using a 5-ethynyl-2-deoxyuridine-based chemical reaction, only after the emergence of partially disassembled SV40 particles in the cytoplasm. These cytoplasmic particles retain some of the SV40 capsid proteins, VP1, VP2, and VP3, in addition to the viral genome. Thus, SV40 particles undergo discrete disassembly steps during entry that are separated temporally and topologically. First, a partial disassembly of the particles occurs in the ER, which exposes internal capsid proteins VP2 and VP3. Then, in the cytoplasm, disassembly progresses further to also make the genomic DNA accessible to immune detection.